Thermohaline stratification in the Southwestern Tropical Atlantic : from physical processes to acoustic ecology - ASSUNÇÃO, Ramilla Vieira de (2021)
The thermohaline structure of the southwest tropical Atlantic (SWTA) has prime impact on global climate and plays a driving role in the vertical structuring of pelagic habitats. To fill information gaps on the thermohaline structure in the SWTA and to bring insights into the relationships between these physical processes and the distribution of the acoustic energy (proxy of organisms biomass), we took advantage of the two scientific surveys, ABRAÇOS, performed in austral spring 2015 and fall 2017. This thesis is organised over three main scientific objectives. First, we characterise the 3D thermohaline structure of the upper SWTA by applying a Functional Data Analysis (FDA) on temperature and salinity profiles. Our results reveal a clear spatial pattern with the presence of three areas with significantly different thermohaline characteristics. Area 1, located along the continental slope corresponds to the western boundary current system. Area 2, located along the Fernando de Noronha chain corresponds to the South Equatorial Current system and Area 3 behaves as a transition zone between these areas. Second, we examined the feasibility of extracting the upper thermohaline structure from echosounder data. Our results show that, even if the thermohaline structure impacts the vertical distribution of acoustic scatters, the resultant structuring does not allow for a robust estimation of the thermohaline limits. However, studying the proportion of acoustic biomass within each layer provides insights on ecosystem structure in different thermohaline, which led us to investigate the fine-scale vertical relationships between acoustic biomass and other environmental factors, as the third objective. We show that fluorescence, oxygen, current and stratification are important drivers, but that their relative importance depends on the area, the depth range and the diel cycle.